Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Remaja Tentang Kesehatan Reproduksi (Studi di SMK Al-Faruqi) - Hardianti, Sri; Sumianto, Sumianto; Hastuty, Milda; Sari, Resy Kumala; Agnesia, Yoana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The adolescence was period of transition from child to adult, this period devide into three stages:early adolescence, middle adolescence and last adolescence, if in this period they misunderstandhow important of the health reproduction it will be fatal to their life and will disrupt the development of the nation because of that need helath education about right an better of healthreproduction. Aim of this research of being to identify adolescents knowledge before and after by health education of the health reproduction. The design of this research by using One Group Pretest Post- test Design. Sample of this research were student XI second semester at SMK AL-Faruqi. The technique sampling was done in a simple random sampling 21 respondents who met the inclusion criteria. The independent variable is health education and dependent variable isadolescence knowledge about the health of reproduction. The data was collected by using theinstrument biofisiologis before and after giving treatment health education. How to analyze it using by Wilcoxon test with a significant level of P < 0.05. The results showed that adolescents knowledge about health of reproduction before and after gave health education on the subject of the significance level was P : 0.003. The conclusion had the influence that was significant betweenhealth education towards adolescence knowledge about health of reproduction.